Customer Knowledge Enabled Innovation: Analyzing Pricing-Promotion Coordination Mechanism - Guanbing Zhao; Yangyang Qiu; Muhammad Imran; Fazal Manan (Complexity)
Pricing and promotion are two important decisions during the market launch of new consumer electronics products. Nowadays, the pricing and promotion of consumer electronic products are often not made separately but at the same time. This study focuses on the pricing-promotion coordination mechanism of a secondary supply chain of new consumer electronics products (which consists of a manufacturer and a seller). Price and the degree of promotion together affect the demand for products. Manufacturers give sellers a sales target. Manufacturers and sellers set prices and promotions separately, introduce repurchase penalty joint contracts, and establish supply chain profit models to compare and analyze optimal pricing, promotion efforts, and maximum profit of supply chains under different decision-making situations. We prove that the repurchase penalty joint contract can coordinate the supply chain under the assumptions of a single-period game and a multiperiod repeated game. The results show that under the repurchase penalty joint contract, when manufacturers and sellers choose high prices and high promotions at the same time, the supply chain of new consumer electronics products has the largest profit. Finally, numerical experiments are conducted to study the influence of parameters on optimal decision-making and supply chain profits.